Exchange of axial base ligand during the crystallization of rhodol linked chlorocobaloxime. Issue 5 (4th May 2022) - Sarath, S.; Anakha, D. R.; Nguyen, Hung-Huy; Yamuna, R.
Abstract: Synthesis of a novel chlorocobaloxime with rhodol dye as an axial ligand which is linked to the cobalt metal through the base pyridine has been reported. X-ray quality single crystal of 3-(diethylamino)-9-(1, 3-dihydro-1-oxoisobenzofuran-3-yl)-9H-xanthen-6-yl isonicotinate was obtained during the crystallization of this rhodol linked chlorocobaloxime. This compound crystallizes in the triclinic crystal system and the space group of P 1. Crystal packing diagram of this structure reveals a 3-D network due to extensive intermolecular hydrogen bonding. This rhodol linked pyridine base was further characterized by 1 H and 13 C NMR. UV-vis absorption spectrum of this compound revealed an absorption peak in the visible region of 515.5 nm. This compound is 25 nm red shifted compared to the precursor rhodol chromophore. Upon excitation at 515 nm, this molecule reveals a strong fluorescence emission at 545 nm.